Designs of rectangular-shaped planar Inverted-F antennas at mobile operating frequencies with different ground plane techniques - Nurul Inshirah Mohd Razali; Norhudah Seman; Tien Han Chua (Institute of Advanced Engineering and Science, 2019)
This article presents the designs of planar inverted-F antennas (PIFAs) at frequencies of 0.835 GHz, 0.9 GHz, 1.8 GHz, 1.9 GHz, 2 GHz, and 2.6 GHz. Initially, the designs of rectangular-shaped PIFAs are determined through the parametric studies concerning the dimensions of the antenna’s patch length, shorting plate, ground plane, and substrate. Afterward, rectangular-shaped slots are introduced into radiating element of two antennas that operate at a lower frequency range of less than 1 GHz, to tune the resonant frequency to the respective 0.835 GHz and 0.9 GHz. Different configurations of partial or full ground plane are implemented to improve the reflection coefficient, S11 performance to be below -10 dB in both simulation and measurement. The proposed six PIFAs have gain that are greater than 2 dB with the nearly omnidirectional radiation patterns. All the designs and analyses are performed using the CST Microwave Studio utilizing Rogers 4003C substrate.